Antigen Binding to Secretory Immunoglobulin A Results in Decreased Sensitivity to Intestinal Proteases and Increased Binding to Cellular Fc Receptors - Duc, Mélanie (American Society for Biochemistry and Molecular Biology, 2010)
In intestinal secretions, secretory IgA (SIgA) plays an important sentinel and protective role in the recognition and clearance of enteric pathogens. In addition to serving as a first line of defense, SIgA and SIgA·antigen immune complexes are selectively transported across Peyer's patches to underlying dendritic cells in the mucosa-associated lymphoid tissue, contributing to immune surveillance and immunomodulation. To explain the unexpected transport of immune complexes in face of the large excess of free SIgA in secretions, we postulated that SIgA experiences structural modifications upon antigen binding. To address this issue, we associated specific polymeric IgA and SIgA with antigens of various sizes and complexity (protein toxin, virus, bacterium). Compared with free antibody, we found modified sensitivity of the three antigens assayed after exposure to proteases from intestinal washes. Antigen binding further impacted on the immunoreactivity toward polyclonal antisera specific for the heavy and light chains of the antibody, as a function of the antigen size. These conformational changes promoted binding of the SIgA-based immune complex compared with the free antibody to cellular receptors (FcαRI and polymeric immunoglobulin receptor) expressed on the surface of premyelocytic and epithelial cell lines. These data reveal that antigen recognition by SIgA triggers structural changes that confer to the antibody enhanced receptor binding properties. This identifies immune complexes as particular structural entities integrating the presence of bound antigens and adds to the known function of immune exclusion and mucus anchoring by SIgA.